Determinants of social capital formation among organic and conventional smallholder producers in Karnataka, India - Vishwanath Gowdru Nithya; Ravi Nandi; Wolfgang Bokelmann (Agricultural Economics Research Review, 2023)
The organic farming aims to create a sustainable agricultural production system. The notion of organic farming extends beyond particular agronomic practices to encompass cooperation and networking among stakeholders. This paper describes findings from a survey conducted with 200 smallholder producers in Indian state of Karnataka with an objective to examine social capital formation in different networks of organic and conventional farming systems. First, we determine the factors that motivate social capital (cognitive and structural) formation among organic and conventional farmers; and then analyze their social capital levels focusing on micro-level cognitive and structural capital. The results reveal a significant difference between both the two communities in respect of social trust, collective action, associated-ness and satisfaction, and these make us to conclude that the organic farmers have a higher level of participation in different formal, informal and social organizations than do the conventional farmers. Overall, the organic farming community is at a higher level of social capital compared to the conventional farming community. Further, within the organic farming community those having higher social capital have effective market linkages than the farmers with lower social capital.